Water quality monitoring and control process by chemical fiber optic sensors - Orellana Moraleda, Guillermo (2010)
Our research team, in collaboration with the company Grupo Interlab, S.A. (Madrid), has been involved in an ambitious project for several years that has brought to the market an optoelectronic instrument for environmental and industrial analysis and control. The multichannel system uses optical fiber sensors and biosensors based on specific indicators resulting from molecular and photochemical engineering of luminescent Ru(II) complexes. In this way, a novel device has been achieved capable of simultaneously monitoring optically, in situ and continuously, various essential parameters in water quality and industrial processes (oxygen, temperature, pH, ammonium, BOD, hydrocarbons, detergents and pesticides). carbamate type) by simply changing the sensitive terminal located at the end of the optical fiber, since all the custom-made indicators are excited by the same light and emit luminescence in the same spectral region. The presentation will detail the path followed from the design and preparation of the latter to the field validation of the developed devices.